Theory and Practice of the Use of Metronidazole Topical Preparations in Dermatology - V. I. Kocherovets (Антибиотики и Химиотерапия, 2020)
The purpose of the study is to analyze the information database of periodicals and monographs on the efficacy and safety of metronidazole medications for external use in the process of local therapy of skin diseases in the Russian Federation. Material and methods. The review includes works of foreign and domestic researchers on the development and clinical use of metronidazole in modern medical practice. Results. Updated clinical and pharmaceutical characteristics of metronidazole preparations for systemic and topical use in diseases of the skin and soft tissues are considered. It has been established that the algorithm for the medicinal use of metronidazole in dermatology differs from that in surgery, therapy, obstetrics and gynecology, and pediatrics. Peculiarities of the modern interpretation of metronidazole mechanism of action as one of topical drugs in the treatment of acne and rosacea are noted. In these cases, metronidazole has an additional therapeutic effect due to mediated mechanisms that do not manifest with systemic use. Conclusion. Despite comprehensive information on the systemic effect of metronidazole, the etiopathogenetic and pharmaceutical features of the use of topical drugs in the treatment of acne and rosacea are not fully reflected in the domestic literature. The inexplicable therapeutic effect of topical preparations should be considered and analyzed in many respects beyond their antimicrobial activity. This is due to the fact that the alleged pathogenetic mechanisms and causes of a number of diseases in which the aforementioned drug is used are poorly studied or not known at all. The indicated features of the use of metronidazole topical preparations in dermatology require the continuation of clinical studies to evaluate the efficacy and safety of the drug, as well as the updating and harmonization of its clinical and pharmaceutical characteristics in the light of modern achievements in medical science.